Emotional regulation and suicidal ideation—Mediating roles of perceived social support and avoidant coping - Gupta, Soham; Fischer, Jonathan; Roy, Sakhi; Bhattacharyya, Atreyee (Frontiers in Psychology, 2024)
Recent research has uncovered a wide prevalence variation of suicidal ideation in university students ranging from 9.7% to 58.3%. India has witnessed a 4.5% increase in suicide rates in the year 2021. The interplay between cognitive reappraisal of a stressful situation, suppression of emotional expression, and coping strategies for suicidal ideation of Indian University students is yet to be explored. We aim to determine whether suicidal ideation would differ across different types of family units, and to predict the extent to which perceived social support and avoidant coping could mediate the relation between emotion regulation processes and suicidal ideation. 200 randomly selected University students (Mean age =19.9, SD =1.43) participated. Kruskal-Wallis, Pearson's product-moment correlation, and GLM mediation model were computed. Lifetime suicidal ideation significantly differed between those who stay alone and those who live in a nuclear family (p < .01), and also those who stay in a joint family (p < .05). Cognitive reappraisal predicted a reduction in suicidal ideation mediated by perceived social support (B = -0.06, p < .05) and avoidant coping (B = -0.07, p < .05). Whereas, expressive suppression predicted induced levels of suicidal ideation through perceived social support (B = 0.05, p < .05), and avoidant coping (B = 0.06, p < .05) as mediators. Though our sample size restricts the generalization, our findings implied the importance of regular psychological consultation regarding the efficacy of the said coping processes in dealing with suicidal ideation.